اسهام المؤسسات التربوية في تنمية القيم الأخلاقية من منظور اسلامي - بن نويوة, سعيد; خماد, محمد (جامعة الوادي - University of Eloued, 2018)
اهتمت الشريعة الاسلامية في اكساب وتنمية القيم الأخلاقية لدى الناشئة بمختلف الأساليب الممكنة من خلال العبادات المفروضة أو القدوة أو القصة أو أسلوب الوعظ والارشاد وعن طريق اسهام مؤسسات التنشئة الاجتماعية والتربوية بمختلف أنواعها. ومن خلال هذه المداخلة سنتطرق إلى تعريف القيم الأخلاقية وإلى خصائص القيم الاسلامية والتعرف على مصادرها. ثم التطرق إلى اسهام مؤسسات التنشئة الاجتماعية والتربوية من المسجد والمدرسة والأسرة والاعلام في اكساب القيم الأخلاقية الاسلامية لدى الناشئة Islamic law is concerned with the development and development of ethical values among young people in various possible ways through obligatory worship, example, story, preaching and guidance. Contribution of institutions of social and educational upbringing of all kinds. Through this intervention we will address the definition of moral values and the characteristics of Islamic values and identify their sources. And then to address the contribution of institutions of social and educational upbringing of the mosque, school, family and media in the moral values of Islamic ethics of the emerging
مقال في مجلة السراج في التربية وقضايا المجتمع بجامعة الوادي
Keywords: مؤسسات تربوية؛ قيم؛ قيم أخلاقية؛ منظور اسلامي: educational institutions; values; moral values; an Islamic perspective